Transformation Of Human Rights Under The Influence Of Digitalization - V. Gaivoronskaya, Yana (2021)
The article shows that, throughout the evolution of human civilization, it shows that the list and scope of rights and freedoms demanded by society change with each new stage of technical and, consequently, economic development. With the formation of a digital civilization, a new round in the development of the human rights institution can be expected. In the research content, the authors highlight the threats and risks to the institution of human rights from the digital transformation of society's normative values and foundations.